An Integrative Theoretical Approach to Property Law and Social Literacy for the Protection of Community Property Rights - Mustofa, Zaenal; Zulkifli, Aiman Hakim bin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
At present, legal protection of property has not been normatively integrated with public legal literacy, resulting in legal certainty over ownership rights that has not been effective in preventing disputes and violations of property rights at the social level. This study aims to propose the concept of an Integrative Theory of Property Law and Social Literacy for the Protection of Community Property Rights. The research employs a conceptual approach through literature review and normative legal analysis to synthesize agrarian law concepts, social literacy, and legal protection theory in order to formulate an integrative model of community property rights protection that is effective both juridically and socially. The findings indicate that the protection of property rights within the Indonesian property law system has not yet been fully effective, as it remains heavily reliant on a normative–formal approach that emphasizes administrative legality, while the dimensions of social literacy and the legal culture of society have not been systematically integrated. Through a conceptual reconstruction based on the Basic Agrarian Law (UUPA), this study affirms that property rights are not merely a juridical status guaranteed by the state, but also a social relationship that requires public understanding, awareness, and active participation for legal protection to function in practice. Social literacy is shown to serve as a preventive protective instrument that strengthens certainty and justice of property rights prior to the emergence of disputes, while simultaneously acting as a bridge between legal norms and social practices. Therefore, an integrative theoretical model that combines agrarian law, socio-legal literacy, and legal culture offers a more substantive, collaborative, and sustainable framework for the protection of property rights, and provides a theoretical and normative foundation for policy development, legal education, and reform of the property rights protection system in Indonesia.